Propulsion systems for hybrid vehicles - Miller, John M. 1949- (Institution of Engineering and Technology, 2004)
The book reviews developments in the following fields: hybrid vehicle characterisation; hybrid architecture; hybrid power plant specification; electric drive system sizing; power electronics for AC drive; drive system control; drive system efficiency; hybrid vehicle test and validation; and energy storage technology.